4‐ary 14/16 modulation code for reducing two‐dimensional inter‐symbol interference. Issue 8 (1st May 2020) - Kim, Juri; Jeong, Seongkwon; Lee, Jaejin
Abstract : Holographic data storage (HDS) can access data in a short amount of time and can also quickly transmit data because HDS records and reads data in units of pages. Thus HDS is regarded as a promising candidate for future optical recording storage systems. Conventional storage systems such as CD, DVD, and HDD have one‐dimensional (1D) inter‐symbol interference (ISI). However, HDS has a 2D ISI that degrades performance. In this study, to avoid and overcome the 2D‐ISI problem, the authors propose a 14/16 modulation code for 4‐ary HDS systems which represents 2 bits on each pixel. The proposed 14/16 modulation code allows a bit of unwanted ISI cases in order to raise the code rate, but it has a higher code rate but similar performance compared to a 3/4 modulation code that has no unwanted ISI cases.